Vibrations of precast and partially prestressed floor systems under moving loads: development of a dynamic fork-lift truck model for vibration serviceability analysis and its application - Ehland, A (2009)
This project studies the dynamic response of a composite floor system to excitations from moving fork-lift trucks. The floor system analysed is a system of precast and partially prestressed double-tee elements with a cast in-situ topping. Currently, there are concerns whether the vibrations caused by fork-lift trucks might exceed acceptable limits due to an ongoing trend towards structures of higher slenderness. This study investigates the mechanical background of the excitation and the current design of the floor system. The study is divided into three major chapters: Dynamic fork-lift truck model A dynamic load model of a fork-lift truck is developed which can be used in the analytical verification of the vibration serviceability of structures. The model is based on tests performed on four fork-lift trucks in various configurations. The tests are analysed for the spectrum of accelerations. The analysis results in a simple two-degree-of-freedom model. Its only variables are velocity and time. All other values are constant throughout a simulation and depend on the geometry of the specific fork-lift truck and its payload. The frequencies and phase delays are constants and they are verified as eigen-frequencies of a three-degree-of-freedom model. FE-simulation of vibrations of a composite floor system The fork-lift truck model is applied to a three-dimensional model of a composite floor system. The finiteelement model is developed to simulate the construction process of the composite floor system and its influence on the in-service properties of the structure. As part of this work a preliminary investigation of the damping potential of the joint between precast and cast in-situ concrete is undertaken. A linear time-step analysis of the structure is performed and the nodal accelerations are analysed for their magnitude, dependence on the excitation and frequency content. Field test In order to verify the FE-model of the floor system and the results of the dynamic analysis a field test was undertaken: a floor system was monitored under service conditions. The field data comprise the accelerations of the floor and the forklift truck and the position of the truck relative to the points of measurement. A comparison of the field data and the simulation results proves the validity of both the dynamic fork-lift truck model and the FE-model of the floor system.